Evolution of strain diversity and virulence factor repertoire in pediatric Staphylococcus aureus isolates - Margaret Free; Nicole Soper; James C. Slaughter; Andries Feder; Colleen Bianco; Ahmed M. Moustafa; Paul Planet; C. Buddy Creech; Isaac Thomsen (PLoS ONE, 2025)
Background Invasive Staphylococcus aureus infections cause high morbidity and mortality in children and adults. With rising antimicrobial resistance, optimal prevention strategies and novel therapeutics are needed. As an effective vaccine remains elusive, characterization of invasive isolates over time is required to identify determinants of invasive infection. Methods S. aureus isolates recovered from children with invasive infection and those with colonization were obtained. Isolates were examined by whole genome sequencing to evaluate gene repertoire, sequence type, clonal complex, and phylogenetic characterization, and isolate characteristics were correlated to clinical data. Results 118 children with invasive S. aureus infections were enrolled; 56% of infections were caused by methicillin-susceptible S. aureus (MSSA). Methicillin-resistance (MRSA) was associated with increased inflammation, though clinical outcomes of MRSA vs MSSA did not differ. Colonization isolates exhibited higher sequence type diversity than invasive isolates. Nine distinct clonal complexes (CC) were identified among all isolates; CC8 and CC5 were associated with higher clinical severity scores. Accessory gene regulator locus type 1, Panton-Valentine Leukocidin, and arginine catabolic mobile element declined over time. Staphylokinase and leukocidin ED were associated with invasive infection, while enterotoxin B was more frequent in colonizing isolates. Conclusions We observed a significant expansion in sequence type diversity among invasive clinical isolates over 12 years with the emergence of newly invasive clones in recent years. The presence of staphylokinase and LukED were associated with invasive infection over time. These findings provide insights into the pathogenesis of invasive S. aureus and may provide putative targets for immunologic approaches to prevention.